2016
DOI: 10.1016/j.neuroimage.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adaptation on numerosity decoding in the human brain

Abstract: Psychophysical studies have shown that numerosity is a sensory attribute susceptible to adaptation. Neuroimaging studies have reported that, at least for relatively low numbers, numerosity can be accurately discriminated in the intra-parietal sulcus. Here we developed a novel rapid adaptation paradigm where adapting and test stimuli are separated by pauses sufficient to dissociate their BOLD activity. We used multivariate pattern recognition to classify brain activity evoked by non-symbolic numbers over a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 65 publications
(83 reference statements)
13
62
0
Order By: Relevance
“…While this strategy is commonly used in studies on numerosity perception, it does not control for differences in the total amount and distribution of contrast energy across numerosities, which is likely to affect early visual responses. This factor may indeed likely account for the early visual cortex activation results in this and other studies, also potentially suggested by a previous fMRI study on numerosity perception, which, after equating the contrast energy of the stimuli, could successfully decode numerosity in parietal but not early visual cortex (Castaldi et al, 2016).…”
Section: Separate Representational Codes For Number and Lengthsupporting
confidence: 72%
“…While this strategy is commonly used in studies on numerosity perception, it does not control for differences in the total amount and distribution of contrast energy across numerosities, which is likely to affect early visual responses. This factor may indeed likely account for the early visual cortex activation results in this and other studies, also potentially suggested by a previous fMRI study on numerosity perception, which, after equating the contrast energy of the stimuli, could successfully decode numerosity in parietal but not early visual cortex (Castaldi et al, 2016).…”
Section: Separate Representational Codes For Number and Lengthsupporting
confidence: 72%
“…However, independent of the execution of such numerical operations, enhanced activity for numbers as opposed to letters or colors was also to a lesser extent measured in HIPS during an orthogonal target detection task (Eger et al, 2003). Moreover, parietal regions were reported to habituate to repeated presentation of the same numerical quantity and show numerical distance-dependent recovery of activity for deviant numbers Cantlon et al, 2006;Ansari et al, 2006b) to some extent even across formats (Piazza et al, 2007;Vogel et al, 2017), to encode numerical quantity in multi-voxel patterns of evoked activity (Borghesani et al, 2018;Bulthé et al, 2014;Castaldi et al, 2016Castaldi et al, , 2019Cavdaroglu and Knops, 2018;Damarla and Just, 2013;Eger et al, 2009Eger et al, , 2015Lasne et al, 2018) and to contain topographically organized numerosity maps (Harvey et al, 2013;Dumoulin, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 97%
“…Hence, common BOLD increase in numerical tasks does not necessarily imply that the underlying representation for different formats and modes is the same. Yet, human imaging studies using multi-voxel pattern analysis (MVPA) endorse simultaneous numerosity encoding independent of response/task related processing (Bulthé et al, 2014;Castaldi et al, 2016;Dormal et al, 2010;Eger et al, 2013Eger et al, , 2009). Based on BOLD signal patterns from PPC these authors were able to decode the numerosities seen by the participants using MVPA.…”
mentioning
confidence: 99%